English Reading Materials with Islamic Materials and Values at Islamic Boarding Schools-Based Communicative Language Teaching - Dedi Efrizal (Linguists : Journal Of Linguistics and Language Teaching, 2023)
Mastery of English in the era of digital-based communication and technological advances is very important for students at Madrasah Aliyah of Darussalam Islamic Boarding School, Kepahiang, Bengkulu. Unfortunately, the students are used to memorizing grammar structures (Nahwu and Shorof) when learning Arabic, and when learning English, especially in reading skills, they are more likely to memorize and prioritize grammar than the flexibility to explore language and convey it into spoken and written language. Then, the teaching materials used by the English teacher as learning media in English subjects, especially in reading competence, tend to focus more on and burden students with grammatical patterns and do not develop students' skills in reading based on experience, the context of life, or their needs in communicating. This study aimed to assist in the implementation of the results of the development of English reading materials with Islamic materials and values for students at Islamic boarding schools based on Communicative Language Teaching to reduce the problems faced by students in learning English reading. This research used the Participatory Action Research method, which looks for something to link the research process to the process of social change. Through several stages of the activity cycle, starting with planning, implementing, observing, and reflecting, which are implemented on the subjects assisted by the students through activities planned in a participatory manner by stakeholders, teachers, and students, The results of the implementation of English teaching materials that occur can be concluded to be that students are able to identify problems in terms of the learning process, share experiences they have gained from previous learning activities, solve problems with solutions they consider strategic, slightly recognize that they need empowerment, and understand that every human being has the potential to be able to communicate in English, depending on their willingness to hone skills and improve abilities.